1998
DOI: 10.1590/s0100-879x1998000600015
|View full text |Cite
|
Sign up to set email alerts
|

Increase in skeletal muscle protein content by the ß-2 selective adrenergic agonist clenbuterol exacerbates hypoalbuminemia in rats fed a low-protein diet

Abstract: This investigation examined how the nutritional status of rats fed a low-protein diet was affected when the animals were treated with the ß-2 selective agonist clenbuterol (CL). Males (4 weeks old) from an inbred, specific-pathogen-free strain of hooded rats maintained at the Dunn Nutritional Laboratory were used in the experiments (N = 6 rats per group). CL treatment (Ventipulmin, Boehringer-Ingelheim Ltd., 3.2 mg/kg diet for 2 weeks) caused an exacerbation of the symptoms associated with protein deficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Of the 11 horses with the lowest [TCO2] there was nothing remarkable about medications or feeding regimen, although 3 horses were on lasix and 3 on ventipulmin. Ventipulmin, a b2 adrenergic agonist, could contribute to lowering TCO2 by lowering pCO2 (Rose et al 1983); however, b2 adrenergic agonists have been shown to increase plasma volume expansion (Ewaldsson et al 2006) and also potentially induce hypoalbuminaemia (Sawaya and Lunn 1998), both of which would act to decrease [Atot]. Therefore, the ventipulmin is not likely responsible for the lowered TCO2 and increased [H + ] in these horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 horses with the lowest [TCO2] there was nothing remarkable about medications or feeding regimen, although 3 horses were on lasix and 3 on ventipulmin. Ventipulmin, a b2 adrenergic agonist, could contribute to lowering TCO2 by lowering pCO2 (Rose et al 1983); however, b2 adrenergic agonists have been shown to increase plasma volume expansion (Ewaldsson et al 2006) and also potentially induce hypoalbuminaemia (Sawaya and Lunn 1998), both of which would act to decrease [Atot]. Therefore, the ventipulmin is not likely responsible for the lowered TCO2 and increased [H + ] in these horses.…”
Section: Discussionmentioning
confidence: 99%
“…1983); however, β 2 adrenergic agonists have been shown to increase plasma volume expansion (Ewaldsson et al . 2006) and also potentially induce hypoalbuminaemia (Sawaya and Lunn 1998), both of which would act to decrease [A tot ]. Therefore, the ventipulmin is not likely responsible for the lowered TCO 2 and increased [H + ] in these horses.…”
Section: Discussionmentioning
confidence: 99%
“…Clenbuterol (CB), which is a β 2 ‐agonist, is used pharmaceutically as a cough suppressant. In addition, the drug has been added illegally into the feedstuff of livestock to enhance animal growth and increase feeding efficiency by inhibiting fat synthesis, stimulating lipolysis, increasing protein synthesis, and carcass leanness . Long‐term or high‐dose use has been shown to illicit deleterious physiological side effects .…”
Section: Introductionmentioning
confidence: 99%